Article Review: The Hepatic Physiology and Pathophysiology of Different Types of Hepatitis - Rashied, Rashied Mohammed; Fouad Kasim, Hala; A. Rahman, Sabah A. Hamid (Journal for Research in Applied Sciences and Biotechnology, 2024)
Globally, viral hepatitis is a frequent cause of liver disease with high morbidity and fatality rates. Since the liver produces a large number of hematopoietic factors and carries out numerous essential tasks that influence metabolism throughout the body. The purpose of this study is to identify hematological complications in patients with acute viral hepatitis. This information will be useful for treating and monitoring these patients. Also, everyone should be aware of the symptoms of hepatitis. Due of this, this article.